PEMETAAN SUB-SUB SEKTOR PERTANIAN DALAM RANGKA PENGEMBANGAN PEREKONOMIAN DAERAH KABUPATEN WONOSOBO - Restika Oki Nindhitya (Economics Development Analysis Journal, 2013)
The purpose of this study to analyze the sub-sectors superior of agriculture are most strategic to be developed in each district to support economic growth in Wonosobo regency. The analysis tools is the Location Quotient (LQ), Shift Share, Klassen Typologi, schallogram, and Overlay. The results showed superior agricultural sub-sectors in each district Wonosobo food crops sub-sector is located in the District Sapuran, Kaliwiro, Sukoharjo, Selomerto, and Mojotengah. Livestock sub-sector in Sub Kertek, and Wonosobo. Forestry sub-sector located in the District Sapuran, Kalibawang, and Kaliwiro. Area food crops sub-sector development in Sub Sapuran, Kaliwiro, Sukoharjo, Selomerto, and Watumalang, while the industrial centers of food crops sub-sector located in the District Sapuran. Area livestock sub-sector development in Sub Kertek, and Wonosobo, while the livestock sub-sector industrial centers located in the District Kertek. Area forestry sub-sector development in Sub Sapuran, Kalibawang, and Kaliwiro, while the forestry sub-sector industrial centers located in the District Sapuran. Development of the agricultural sub-sector seed production centers do with the construction and industrial centers. By observing the superior agricultural sub-sector, the value schallogram and GDP per capita, it can be determined the development direction of each sub-sector of agriculture, by determining the area of production centers and industrial centers